(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: One of the most important activities at universities among students is scientific research, especially with the development of science and technology nowadays. Objectives: To conduct a survey on the rate and readiness level to participate in scientific research activities of the students of the University of Medicine and Pharmacy at Ho Chi Minh City and point out some related factors. Methods: Descriptive cross-sectional study on students of various majors at University of Medicine and Pharmacy at Ho Chi Minh City in the 2024-2025 academic year. We conducted a survey through an online questionnaire. Results: The study recorded 5.312 students taking the survey, showing that 31,08% of students “strongly agree” and 49,83% “agree” with the importance of scientific research activities among students. 90,05% of students had already known about scientific research activities, of which 22,2% of students had participated or were participating in a scientific research activity. Among the group of students who have known and have participated or are participating in scientific research activities, the most popular form of participation is "essays, topics for specialized subjects" with 23,10% of students participating, followed by “graduation thesis, Faculty-level research topics” accounting for 22,34%. Conclusions: Students highly agree with the importance of scientific research (80,91%), over 90% of students know about scientific research activities, but only 22,2% of students have participated or are participating in a scientific research activity, this rate varies between faculties.